An investigation into the role of firm-level multinationality in international portfolio diversification - CHADHA, PEARLEAN (Trinity College Dublin. School of Business. Discipline of Business & Administrative Studies, 2018)
The Multinational Corporation (MNCs) as an alternative to direct international diversification has received the attention of International Business (IB) and International Finance (IF) scholars for decades. Investing in MNCs as a vehicle for achieving the benefits of international diversification has shown mixed and incomparable results. This incomparability reflects a lack of consensus among IB and IF scholars on how to measure firm-level multinationality. This thesis provides an investigation into the role of firm-level multinationality in indirect international diversification benefits for equity investors from the U.K. and Japan. I examine the scale and scope of a firm's operations by compiling a longitudinal dataset of the location of a firm's sales and subsidiaries over the 18-year time-period 1998-2015. The dataset consists of firms listed on the Nikkei 225 index for Japanese investors and FTSE 350 for U.K. investors. The dataset is used to address three areas in the IB and IF disciplines and the results provide alternative perspectives to existing topics within the literature. First, an investigation into the changing patterns of firm-level multinationality contributes to the growing debate on the regionalisation versus globalisation of firms. Second, the analysis of domestic, global and regional influences on firm returns contributes to the issue of how the geographic spread of sales and subsidiaries is reflected in company returns. Finally, the analysis of firm-level multinationality and indirect foreign exposure available to investors from domestically traded firms provides new insights into the home bias phenomenon. This phenomenon indicates that investors favour domestic investments, over direct international diversification. I first study the level of internationalisation of firms from the U.K. and Japan and analyse the changing the patterns of firm-level multinationality over time. I construct a hand-collected dataset of each firm's location of sales and subsidiaries in each year. I find no evidence of regionalisation as suggested in the existing literature (Rugman, 2003; Dunning et al., 2007; Verbeke & Kano, 2016) with a majority of the sample following a trans-regional strategy with operations spreading to regions outside their home-region. I also find evidence that the concentration of firms' operations is in the Triad regions of North America, Europe and Asia, but there is growing number of firms expanding to non-Triad regions. My results show that firms are more multinational based on the measure of subsidiaries than sales and contradict the traditional theories of internationalisation which focuses on firms expanding trade first and then investments. Next, I use the linear factor models to analyse the domestic, global and regional influences on a firms' returns. I use the firm-level multinationality dataset to investigate the influences on firms' returns with varying degrees of internationalisation. I also analyse individual firms' returns to investigate whether the geographic spread of operations is reflected in the stock return and how this pattern evolves over the 18-year time-period. The results show that all categories of firms are influenced by the domestic factor rather than the global factor. Firms with operations only in their home-country are an exception as they are influenced by both domestic and global factors. This suggests that firms with less diversified operations are exposed to global market movements while well-diversified firms remain immune. The firms in my sample also have significant exposure to their home-region demonstrating the influence of geographically closer markets versus those which are further afield. The findings show that the geographical spread of operations is not reflected in the firm returns as firms are influenced by geographic regions where they do not have operations. This suggests that analysing the geographic spread of firm's sales and subsidiaries does not give investors accurate information on the influences on stock returns. Finally, I use mean-variance spanning tests and Sharpe Ratio analysis to compare the benefits of investing in firms with varying degrees of international involvement and foreign exposure, from the perspective of local investors in the U.K. and Japan. I find that there are benefits for these investors to include multinational firms in their portfolios but not necessarily firms with greatest level of global operations. The benefits of investing do not increase with increasing levels of multinationality. The results also show significant benefits of investing in firms with exposure to geographic regions rather than firms with operations in those regions. I also find that investing in firms that are significantly influenced by a geographic region in which they do not have operations, offers investors good diversification benefits. This suggests that investors should analyse the geographical influences of firms' return rather than the location of operations, when making investment decisions. This thesis makes a number of empirical contributions to the existing IB and IF literature. I provide a valuable longitudinal dataset of firm-level multinationality based on both sales and subsidiary data. Through an in-depth analysis of internationalisation patterns using both accounting and non-accounting data, I advance the debate surrounding regional or global strategies adopted by MNCs. The analysis of geographical influences on firm returns combined with the extent of firms' international operations, contributes to the existing literature on domestic versus global versus regional factors. The firm-level analysis of changing exposure to regional factors in combination with the geographic location of sales and subsidiaries shows that the exposure to international factors is not reflected in the corporate diversification of firm operations. I also conclude that the greatest indirect international investment benefits lie in the analysis of geographical influences on firm returns and not a simple analysis of the location of operations. Investors should be aware of the international exposure embedded in their domestic equity portfolios. Individual equity investors and portfolio managers should carry out a thorough analysis of the foreign exposure of stock returns and incorporate these results in the initial stages of the investment allocation process to gain maximum benefits of indirect international diversification. This innovative portfolio allocation strategy can make the home bias attribute among investors a more well-informed one.
APPROVED